The impact of the ketogenic diet on the course of schizophrenia and bipolar disorder - Klaudia Klimczak; Agnieszka Protasiuk; Agata Żak-Gontarz; Rafał Sierzpowski; Patrycja Tymoszuk; Bartosz Kasperek; Katarzyna Augustowska; Kamila Budzyńska; Laura Loryś (Quality in Sport, 2025)
Introduction and purpose